2020
DOI: 10.1038/s41598-020-76306-9
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and the risk of abdominal aortic aneurysm: a systematic review and meta-analysis of prospective studies

Abstract: The association between physical activity and risk of abdominal aortic aneurysm has been inconsistent with some studies reporting a reduced risk while others have found no association. We conducted a systematic review and meta-analysis of prospective studies to quantify the association. PubMed and Embase databases were searched up to 3 October 2020. Prospective studies were included if they reported adjusted relative risk (RR) estimates and 95% confidence intervals (CIs) of abdominal aortic aneurysm associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Last, the study did not investigate risk factors that have an association with AAA but that are often not routinely coded in primary care, such as physical activity. 36 The causality of physical activity, and other risk factors, in the prevention of AAA require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Last, the study did not investigate risk factors that have an association with AAA but that are often not routinely coded in primary care, such as physical activity. 36 The causality of physical activity, and other risk factors, in the prevention of AAA require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exercise is generally safe for, and well tolerated by, patients with small AAAs and does not influence growth rates, but may reduce the risk of AAA development [ 133 , 134 , 135 ]. A well-balanced diet may reduce the risk of AAA, but studies analyzing diet quality in AAA patients are scarce [ 136 , 137 ].…”
Section: Risk Factors and Comorbiditiesmentioning
confidence: 99%
“…Physical activity could reduce the risk of aortic diseases because it has a beneficial effect on cardiovascular risk factors such as hypertension and arterial stiffness as well as an anti-inflammatory effect [17][18][19][20][21] . A previous meta-analysis of prospective studies suggested that higher levels of physical activity were associated with a reduced risk of aortic diseases; however, only five of nine studies showed no association, and three of five studies did not adjust for major confounders such as smoking, obesity, and hypertension 22) .…”
Section: Discussionmentioning
confidence: 91%
“…Our findings support the results of a metaanalysis of prospective studies on the association between physical activity and incidence of or mortality from abdominal aortic aneurysm. The summary relative risk for high versus low physical activity was 0.70 (95% CI: 0.56-0.87) 22) . However, in the abovementioned meta-analysis, no study on physical activity and mortality from aortic aneurysm showed a significant association between the two.…”
Section: Resultsmentioning
confidence: 99%